Mapping Strategies of Net Working Capital in the Energy Sector in Poland – Transformation Perspective - Walicka, Monika (Mapowanie strategii kapitału obrotowego netto w sektorze energetycznym w Polsce – perspektywa transformacji, 2024)
The aim of the article is to identify net working capital management strategies used in the energy sector. The analysis covered all companies listed on the Warsaw Stock Exchange under the WIG-Energy industry index. The study was conducted on the basis of financial reports for 2022-2023, with data from the latest reported quarters, i.e. Q1 and Q2 of year 2023, used in strategy mapping. The ratio analysis method was used with reference to industry indicators, and the dynamics of changes in the examined indicators was taken into account. The research results indicate that currently energy entities mainly use agressive strategies (64%). The sector's net working capital forecast indicates that the strong growth trend that has been seen since 2020 will gradually begin to slow down from 2023. As a result of using the indicator mapping technique, significant concentration of indictors can be noted in the sector, with only two entities differing from the rest of the sector in this regard.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 2, s. 51-61
Keywords: net working capital; net working capital management strategies; energy; cash conversion cycle; energy sector transformation; kapitał obrotowy netto; strategie zarządzania kapitałem obrotowym netto; energia; cykl konwersji środków pieniężnych; transformacja sektora energetycznego